Child Health Care: Past, Present, and Way Forward - Mamta Verma; Jyoti; Anamika Khatri; Pragati Kumari; Huzaifa Akram; Shivani Jadaun (Pediatric Review: International Journal of Pediatric Research, 2024)
The current landscape of child healthcare and nursing practices showcases a multitude of innovative approaches aimed at facilitating children's attainment of their maximum functional potential. This article embarks on a historical journey, elucidating the milestones that culminated in the inception and evolution of child healthcare services.